Borderland : formação de professores e práticas de letramento de inglês para alunos surdos - Coelho, Jubileia Mendes de Matos (2017)
The idea of boundary means more than the concepts of boundary, margin, delimitation and displacement. It clutters the sense of approach and movement too. The conceptualization of the border as between-place (ÁGUAS, 2013) - space that unites Borderland - translates place of interaction, movement of sociocultural practices. The Borderland metaphor describes, in this research trajectory, a border space of cultural and linguistic approximation between hearing teachers and deaf students in language teaching. In this bias, the conception of language does not constitute a closed, uniform and indivisible set, but it embraces the idea of inter-place as an open space of social and cultural practices located in reading and writing, that is, literacy practices. The goal is to analyze the experience of teaching English to deaf students. To that end, I examine the training of language teachers. The theoretical reference covers studies of literacy (DUBOC, 2007; DUBOC, 2015; MATTOS, 2015; MONTE MÓR, 2013a; MONTE MÓR, 2013b; MONTE MÓR, 2015; STREET, 2014) and critical literacy (JESUS, 2017; JORDÃO, 2015; JORDÃO, 2016; MENEZES DE SOUZA, 2011a; MENEZES DE SOUZA, 2011b). It also involves additional languages and takes care of some educational demands of deaf students in Brazil, such as bilingual education of two modalities - oral and sign language - and the perspective of differences and not deafness in the same educational context. Methodologically, this study fits within a paradigm of qualitative-interpretative research (BONTONI-RICARDO, 2008; BOGDAN; BIKLEN, 1994). The main instruments for data generation were filming and transcription of classes and interviews, probing questionnaire, classroom activities and participatory observation. The research considered the activities of reading and writing, together with the impressions of the researcher-observer, as well as impressions and meanings attributed by the female teachers on their pedagogical action. The motto that originated this work occurred as a result of the observation of reading and writing literacy practices in language teaching (English), developed by a group of five teachers in the course of Letters of a public university during a supervised stage for two classes of deaf students. These were adolescents, young people and adults, in an initial level of English learning, attending elementary school, high school and youth and adult education. The results showed that English reading and writing literacy practices proved to be a frontier area of interaction with some meaningful learning for deaf students. In this way, it is concluded that the internship practice allowed the participants of this research to constantly revisit their own pedagogical action, throughout the entire stage, and the perception of this practice as a moment of learning. This allows pointing out that the monolingual perspective (ZOLIN-VESZ, 2014; ZOLIN-VESZ, 2015; ZOLIN-VESZ, 2016; ZOLIN-VESZ; LIMA, 2017) can be problematized from a teaching practice that promotes reflexivity, favored by constant mediations and theoretical-methodological questions.